Press clipping and the use of links from the perspective of Copyright - Córdova Mezarina, Jorge (2015)
This paper analyses the protection offered by Copyright to newspaper articles and, from here, it examines the ways in which the articles are used by press clipping companies. Also, the paper presents resolutions related to the use of links to web pages and its relation with possible Copyright law infractions. Finally, the paper analyses a legislative amendment on the subject, which took place in Spain.